Justification of Effectiveness of International Power Interconnections with Separation of Effects between Participants - Podkoval’nikov, S. V.; Savel’ev, V. A.; Khamisov, O. V.; Chudinova, L. Yu (Automation and remote control, 2018)
We consider the methodology and describe the tools needed for a system study of the effectiveness of the development of international power links and the interconnections that are formed as a result, in particular from the point of view of the countries included in them. We give examples where we justify the effectiveness of an international interconnection in the Northeast Asia region.